Care in pregnancies subsequent to stillbirth or perinatal death. (10th December 2020) - Graham, Nicole; Stephens, Louise; Heazell, Alexander EP
Abstract : Key content: Pregnancies following stillbirth have an increased risk of adverse outcome, including a 4.8‐fold increased risk of stillbirth. Risk factors for stillbirth include obesity, smoking, advanced maternal age, fetal growth restriction, hypertension and diabetes. Increased risk of medical problems may result from recurrent placental pathologies or genetic conditions or persistent maternal disease; thus, care for a subsequent pregnancy should commence with investigation of the index stillbirth. Parents also require additional psychological support to navigate mixed emotions, particularly anxiety, about the development of pregnancy complications. Antenatal care in a subsequent pregnancy after stillbirth should ideally be delivered by a multidisciplinary team to provide continuity of physical and psychological care. Learning objectives: To improve understanding of the importance of a preconception/early pregnancy appointment and the key information to be covered in such an appointment in a pregnancy after stillbirth. To know what information can be gained from postnatal investigations and the placental histology report and the relationship between this information and a subsequent pregnancy after stillbirth. To be able to describe an example of a model of care used to address medical and psychological needs of parents in subsequent pregnancy. Ethical issues: Failing to appreciate the medical and psychological significance of a history of stillbirth may lead to suboptimal antenatal care that does not meet women's needs. Lack of robust evidence may lead to prescription of medication without clear evidence of benefit.